Sustainability of Nutraceuticals and Functional Foods - Wichienchot, Santad; Ishak, Wan Rosli Wan (John Wiley & Sons, Inc., 2017)
Sustainability challenges and issues in nutraceuticals and functional foods arena have influenced both consumers and the industrial sector. Though the present day can be termed as an era of nutraceuticals and functional foods, the knowledge on sustainability among the people involved is limited in the pharma‐food industry. In this chapter, we provide a general overview of this subject, followed by discussion on the four pillars of sustainability and how these relate to the agricultural system, food safety and food security. Examples of nutraceuticals products, health benefits incurred, consumer trends and food choices as well as market values are all examined.